Semantic technology and linguistic modelling in business strategy design and evaluation. (21st June 2019) - Stašák, Jozef; Schmidt, Peter
This paper addresses the problem of a knowledge based support, when designing business strategy and adequate key performance indicators (KPI). The business strategy designing is considered to be a business process and is a subject of modelling as well, while a linguistic modelling approach is applied for those purposes, where the business process model semantics plays a role of principal importance and that model is derived from text in natural language (TNL text), which describes structure and functionality of the business processes to be modelled quantified via linguistic sets, which create basis of business process model semantics and might be applied in design and implementation of business process linguistic modelling - expert system built up base on semantic technology principles (ST-LM expert system). The ST-LM expert system knowledge base operates based on semantic networks and (SNW) and reference databases and contains knowledge concerned to KPI Indicator generation and decomposition to lower levels of management. In that paper, the ST-LM expert system structure and functionality is described together with an appropriate knowledge base and inference mechanism.